Water Quality Analysis of Village and Monitoring Well around Rembang Steam Power Plant (EIA in Central Java, Indonesia) - Sunik Sunik; Very Dermawan (IPTEK Journal of Proceedings Series, 2017)
Water quality sampling and monitoring of village well as a regular monitoring each quarter in a year for Rembang Steam Power Plant 2 x 315 MW was one part of EIA implementation study. This research aim to analysis the most impact occurrence that forecasted as a hypothetical important impact which is cause environmental change base on water quality sampling and monitoring from operational activity in first quarter (TW 1). Implementation method was used water sampling in 2(two) resident well and 6 (six) monitoring well in Trahan and Leran village, then the water sample was analyze in laboratory refer to the raw quality which has been set. The monitoring result on the residents wells quality was generally known that in the Trahan village residents wells (AB-1) found parameter that exceed quality standard i.e. total dissolved solids (TDS, come from river seepage and rainfall runoff), Chloride and Hardness,the high concentration some parameters, both exceed the quality standard as well as have a high critical level, generally was not caused by the operational activities of Rembang Steam Power Plant. Monitoring result from 6 (six) monitoring wells in location of Rembang Steam Power Plant was found parameters in several point that exceed the quality standard i.e. Turbidity in AB-3, organic chemical substance (KmnO4) in AB-3 and AB-7, TDS in AB-3 (monitoring wells 1), AB-4 (monitoring wells 2), AB5 (monitoring wells 3) and AB-7 (monitoring well 5), and AB-8 (monitoring wells 6). While the content of heavy metals that detected include arsenic, cadmium, lead, and selenium on AB-3.